Sustainable Fire Retardancy of Cellulosic Materials by Application of Plant Bio-macromolecules - BASAK, S.; SAXENA, SUJATA; RAJA, A. S. M.; PATIL, P. G. (Cotton Research Journal, 2021)
The field of flame retardancy of cellulosic materials like cotton is facing lot of challenges since past few years due to the concerns of eco-friendliness, sustainability, etc. as the quantity of the chemicals used is high, toxic, expensive and have detrimental effect on the strength and hand value of the material surface at required add-on percentage. Therefore, there is a need to find an easy to apply, cheap, eco-friendly fire retardant chemical which can be effective even at low add-on% and has no detrimental effect when applied on the textile material. Scientists and researchers from different fields all over the world are trying to find a solution to this problem. In this regard, recently plant based bio-molecules have been tried for making fire resistant material. In this paper, the effect of various plant based bio-molecules on the fire retardant property of cellulosic textiles and the mechanism behind the thermal stability of the treated textiles has been examined. This review also enlightens us with the thermal kinetics of the textile materials treated with plant based bio-macromolecules.